Analisis Struktur Biaya dan Pendapatan Usaha Rumah Tangga Di Kecamatan Watubangga Kabupaten Kolaka “Studi pada Industri Pembuatan Tahu” - Sabarudin; Sindi Adistri (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
Analysis of the Cost Structure and Income of Household Businesses in Watubangga District, Kolaka Regency (Study on the Tofu Making Industry). This study aims to: analyze the cost structure and income of the tofu making industry so that the "tofu making industry" business actors in Watubangga District, Kolaka Regency do not experience losses. The method used in this research is descriptive qualitative research method with the determination of the research sample using the total sampling method. The data were analyzed using the total revenue formula, the revenue formula, and the total revenue formula. The results show that: the break-even point for each industry where the costs incurred should not exceed Rp. 31,160,390/month, or the minimum average income that must be obtained is Rp. 9,490,633/Month. This can be interpreted that the income earned by the home industry to make tofu can cover all costs incurred during the production of tofu. The tofu industry in Watubangga District, Kolaka Regency is still feasible to run because the industry players do not experience losses during the course of production.